EDUCATION AND IMPLEMENTATION OF THE SUN FILTERED PHOTOTHERAPY AIRLANGGA BILIRUBIN SUN (AIRBILISUN) TO IMPROVE HEALTH WORKERS KNOWLEDGE ON THE MANAGEMENT OF NEONATAL JAUNDICE IN BANYUWANGI, EAST JAVA - Irwanto; Mahendra Tri Arif Sampurna; Andi Hamim Zaidan; Zida Husnina; Martono Tri Utomo; Neurinda Permata Kusumastuti; Muhammad Irvan Avandi; Muhammad Naznuddin; Muhammad Nafik Hadi Ryandono; Egi Azhar Rafsanjani; Syah Reza Budi Azhari; Achmad Rifqi Fannani; Valentinus Mahendra Aaron Quendangen (Universitas Airlangga, 2026)
Neonatal hyperbilirubinemia remains a common condition encountered in primary neonatal care, particularly in settings with limited access to standard phototherapy equipment. In Banyuwangi Regency, gaps in health workers’ knowledge and unequal availability of phototherapy devices contribute to suboptimal management practices, including unsafe reliance on uncontrolled sun exposure. This community service program aimed to strengthen health workers’ capacity in managing neonatal jaundice through education, training, and the implementation of an appropriate technology innovation, the Airlangga Bilirubin Sun (AirBiliSun). The program involved 30 health workers from hospitals and community health centers and was implemented through sequential stages of socialization, training, technology application, mentoring, and evaluation. Participants’ knowledge was assessed using pre-test and post-test questionnaires. Quantitative analysis demonstrated a significant improvement in knowledge following the intervention. The mean knowledge score increased from 58.88 ± 17.56 before the program to 73.77 ± 19.57 after the program. The proportion of participants with poor knowledge decreased from 26.7% to 3.3%, while those with good knowledge increased from 20.0% to 30.0%. Statistical testing confirmed that the improvement was significant (paired t-test, p < 0.001; Wilcoxon signed-rank test, p = 0.041). These findings indicate that combining structured education, hands-on training, and mentoring with the use of appropriate technology can improve health workers’ readiness to manage neonatal hyperbilirubinemia in resource-limited service settings. Institutional support from local government and national downstreaming initiatives further highlights the potential sustainability and replicability of the program. The AirBiliSun community service program demonstrates a practical approach to strengthening neonatal care services and promoting safer management practices in primary health facilities.